Sensitivity analysis of Cattaneo–Christov heat and mass flux model effects in Stefan blowing flow of ferromagnetic nanofluid: Numerical simulations - Fisal Asiri; Sohail Rehman; Nidhal Drissi (Results in Chemistry)
Sensitivity analysis (SA) using response surface methodology (RSM) is frequently used to optimize the efficiency of fluid dynamics research allowing accurate thermal performance, in energy systems, in biomedical applications, and for industrial cooling. Therefore, the objective of this research, is to implement a robust SA in order to predict the relative heat and mass transfer of ferromagnetic tangent hyperbolic nanoluid (NF) over a stretching sheet. The heat and mass transfer efficiency in a thermally mixed convection Stefan blowing flow of NF is optimized by means of RSM. The Cattaneo–Christov heat flux model, Thompson and Troian velocity slip, Stefan blowing, mixed convection effects, in a dynamic magnetic diploe regime are included for the first time in the governing model. The governing model is scrutinized numerically using Runge–Kutta method. The influence of solid-liquid interface layer and nanoparticle movement is highlighted at the molecular level to further uncover the heat amplification of the NF using Buongiorno model. The findings suggest that the Buongiorno model and mixed convection effect have a positive effect on heat transfer enhancement, while the thermal and solutal relaxation have a negative effect on heat and mass transfer rates. The sensitivity of thermophoresis for Nusselt is negative while an opposite scenario was concluded for Sherwood number.